Designing a Framework for Target-Site Assignment in Naval Combat Management - Okhravi, Amirhossein; Pooya, Alireza; Nazemi, Shamsodin; Kazemi, Mostafa (Defence Science Journal, 2016)
In this study, using operational research techniques, a model has been presented to assess battlefield threat, to prioritise aggressive targets, to evaluate the capability of own sites and the risks of the conflict with the targets, to define conflict scenarios and finally to select the best scenario using an assignment model. The above proceedings were added as an intermediate phase of target-site assignment, called ‘deciding the best conflict scenario’, to the ‘threat assessment’ and ‘weapon-target assignment’ in the naval combat management system. For each of the own site, the data collected from the environment together with the panels of experts are shown in a two-dimensional matrix, in which the four areas of the matrix represent the conflict scenarios. Considering that the study was done in a simulated environment, the expert’s verification and the convergence of the results in Monte Carlo method were used to validate the research. The proposed model can offer optimised decision to the operational commander through predicting the battlefield and managing the site’s capacity and the interaction in between during the combat.